(untitled) (Journal of history, 2020)
In this article, the authors summarize the main results of archaeological explorations conducted in the Aral region of the Kyzylorda region in the summer of 2019. During the exploration work, parking sites related to the stone period were identified. In addition, stone tools were collected on the surface of the Stone Age sites. The article discusses the main issues of geology and hemorphology of the North- Eastern Aral Sea region and the history of archaeological research in the region. Paleolithic monuments occupy a special place, first of all, in solving urgent problems of the Paleolithic sites of the Aral Sea region in the Stone Age (development of the Stone Age culture, the evolution of tools, etc.). It also analyzes the discovery and study of the stone age of the century, their periodization. Among the sites opened in 2019, a description is given of stone tools taken from the Saryshoky site, opened in the vicinity of the village of Shomish in the Aral region. Given the topography of the location of the monuments, we observe that the ancient sites are located on the sidelines of the ancient dead wood.